Kinematic analysis of the final stride approach in Spanish elite high jumpers - Mateos-Padorno, C.; García-Manso, J. M.; Fuentes García, J. P.; Martínez-Patiño, M. J. (International Journal of Performance Analysis in Sport, 2021)
In high jumping, the horizontal velocity which jumpers aim to reach by the end of the run-up must be the maximum that they can control, enabling them to clear the greatest height possible. Furthermore, jumpers should reach the point of take-off with the lowest possible centre of mass (CM) to increase the thrust during take-off and thus produce a greater vertical velocity of the CM at the end of this phase. The aim of this study was to identify gender-related differences in the kinematic parameters of the sprint. The sample comprised 14 high jumpers (n = 8 males and n = 6 females) who were analysed during an official competition and recorded with four high speed panning cameras (sampling frequency: 50 fps). The results showed gender-related differences in the maximum height attained by the centre of mass during the flight phase (p = 0.004; Effect Size = 0.93) and in flight effectiveness (p = 0.001; ES = 5.53), but not in jump effectiveness. Gender-related differences were not detected between the trajectory followed by the CM in the final supports of the run-up and the curve radius or in the direction of the final supports either. In conclusion, there are no significant gender differences in the run-up.